Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai PT. PLN (persero) Distribusi Daerah Jawa Tengah dan D.I.Yogyakarta Area Semarang - Rian Oktavianto; Herbasuki Nurcahyanto; Susi Sulandari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The performance of company employees are a way to achieve its goals.Pertaining to performance, motivation and discipline work can be directly to degrade its performance or improve the performance of a clerk.Employees with motivation that are tall and discipline good working will make the employee performance to become more optimal so that it can bring the impact on the performance of employees as a whole.However, contrarily if motivation bad and discipline work less well, also the performance of employees to become not optimum and bring negative effects for the company.In this research, that was performed in PT. PLN (Persero) Distribusi Daerah Jawa Tengah dan D.I.Yogyakarta Area Semarang can be known that the performance of employees still not optimal.It is visible from the attainment of performance that is not based on the target.Purpose in this research is to find out the influence of motivation and discipline work against the employee performance in PT. PLN (Persero) Distribusi Daerah Jawa Tengah dan D.I.Yogyakarta Area SemarangPT. PLN (Persero) Distribusi Daerah Jawa Tengah dan D.I.Yogyakarta Area Semarang can be known that the performance of employees still not optimal.It is visible from the attainment of performance that is not based on the target. The purpose of this research is to know the influence of motivation and discipline work against the performance of employees at PT. PLN (Persero) Distribusi Daerah Jawa Tengah dan D.I.Yogyakarta Area Semarang. The research method used is quantitative research. Data obtained in this study through interviews using koesioner. Analysis of the data used is the coefficient of correlation coefficients of Kendall and concordance of the Kendall. From theresults of research using the SPSS program it can be known that there is a very weak influence motivation (X 1) against the performance of employees (Y) witha coefficient of correlation of kendall tau of 0.040 (under 0.5) with probability figures 0.709 (greater than 0.05); There is a very weak influence on the discipline of work (X 2) against the performance of employees (Y) with a coefficient of correlation of kendall tau of 0.052 (under 0.5) with probability figures 0.633 (greater than 0.05); For the determination coefficient (R2) indicated on the Kendall Ws Coefficient of 0.491.